Landnám, Land Use and Landscape Change at Kagaðarhóll in Northwest Iceland. (4th March 2022) - Bates, Rupert; Erlendsson, Egill; Eddudóttir, Sigrún Dögg; Möckel, Susanne Claudia; Tinganelli, Leone; Gísladóttir, Guðrún
ABSTRACT: Palaeoecological studies from across Iceland, in tandem with historical and archaeological examinations, have helped improve our understanding of patterns and processes involved in the initial settlement of Iceland. Here, we present a new high resolution reconstruction of vegetation and landscape dynamics for the farm Kagaðarhóll, a lowland site in Austur-Húnavatnssýsla, Northwest Iceland, a region with a notable scarcity of known archaeological sites. Through palynology and the analysis of lithological proxies, the study locates and examines human influence at the study site and evaluates the mechanisms of environmental change. Prior to settlement, following long-term vegetation regression, Betula woodland interspersed with sedge bog was prevalent at Kagaðarhóll. Woodland clearance and grazing was initiated no later than AD 900, illustrating the arrival of humans. Over the following centuries, the record shows continued grazing, increased soil erosion and a transition into heathland and shrubland indicative of anthropogenic environmental degradation. Woodland conservation and management practices are also inferred. The study is important in extending knowledge of Icelandic environmental change and anthropogenic activity where archaeological research is scant and in bringing together regional patterns of settlement in order to understand wider settlement processes.